2022
DOI: 10.3390/healthcare11010133
|View full text |Cite
|
Sign up to set email alerts
|

Reporting and Interpreting Effect Sizes in Applied Health-Related Settings: The Case of Spirituality and Substance Abuse

Abstract: Inferential analysis using null hypothesis significance testing (NHST) allows accepting or rejecting a null hypothesis. Nevertheless, rejecting a null hypothesis and concluding there is a statistical effect does not provide a clue as to its practical relevance or magnitude. This process is key to assessing the effect size (ES) of significant results, be it using context (comparing the magnitude of the effect to similar studies or day-to-day effects) or statistical estimators, which also should be sufficiently … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…In summary, authors are expected to systematically report and interpret ESs in studies using inferential statistics, and even more so in randomized, controlled experimental studies. However, based on our previous work in the clinical setting [52,53], we believe that we are not there yet.…”
Section: Null Hypothesis Significance Testing Es and Clinical Signifi...mentioning
confidence: 95%
See 1 more Smart Citation
“…In summary, authors are expected to systematically report and interpret ESs in studies using inferential statistics, and even more so in randomized, controlled experimental studies. However, based on our previous work in the clinical setting [52,53], we believe that we are not there yet.…”
Section: Null Hypothesis Significance Testing Es and Clinical Signifi...mentioning
confidence: 95%
“…Some studies have found that NHST p-values were rarely supplemented with information on ES, despite the existence of published guidelines [50,51]. In the field of substance abuse, a systematic review [52] revealed that 57.9% of the selected studies did not report ES indices, while 47.4% did not interpret the magnitude or relevance of their findings. Similarly, a review examining the effects of physical exercise on depressive symptoms [53] discovered that 52.4% of experimental studies did not report ES indices.…”
Section: Null Hypothesis Significance Testing Es and Clinical Signifi...mentioning
confidence: 99%